Right Lateral Position Can Be Recommended As An Intervention In Heart Failure (HF) Patients To Improve Respiratory Status - Lestari, Lina Rahma; Mohtar, M Sobirin; Gaghauna, Eirene E.M; Riduansyah, Muhammad (Universitas Tribhuwana Tunggadewi, 2025)
Heart failure accounts for 85% of deaths among cardiovascular disease patients. One of the primary complications in heart failure patients is an ineffective breathing pattern. Reducing mortality related to respiratory dysfunction requires fundamental interventions. One effective nursing intervention is patient positioning, which enhances lung expansion and alleviates shortness of breath. This study investigates the impact of the right lateral position on the respiratory status of heart failure (HF) patients at RSUD Dr. H. Moch Ansari Saleh. This study employed a quantitative, pre-experimental research design, specifically a one-group pretest-posttest approach. A total of 30 respondents were selected using a purposive sampling technique. Data collection involved observation sheets based on the SLKI for ineffective breathing patterns and pulse oximetry measurements. Statistical analysis was conducted using the Wilcoxon test, yielding a p-value of 0.000, indicating a significant improvement in respiratory status after the right lateral positioning intervention. These findings suggest that the right lateral position can be an effective nursing intervention to enhance respiratory function in HF patients. Therefore, it is recommended for implementation in the Kumala Room, Floor III, as a supportive measure to improve patient outcomes.